Stimulation and quantification of Babesia divergens gametocytogenesis - Jalovecka, Marie; Bonsergent, Claire; Hajdusek, Ondrej; Kopacek, Petr; Malandrin, Laurence (Parasites & vectors, 2016)
BACKGROUND: Babesia divergens is the most common blood parasite in Europe causing babesiosis, a tick-borne malaria-like disease. Despite an increasing focus on B. divergens, especially regarding veterinary and human medicine, the sexual development of Babesia is poorly understood. Development of Babesia sexual stages in the host blood (gametocytes) plays a decisive role in parasite acquisition by the tick vector. However, the exact mechanism of gametocytogenesis is still unexplained. METHODS: Babesia divergens gametocytes are characterized by expression of bdccp1, bdccp2 and bdccp3 genes. Using previously described sequences of bdccp1, bdccp2 and bdccp3, we have established a quantitative real-time PCR (qRT-PCR) assay for detection and assessment of the efficiency of B. divergens gametocytes production in bovine blood. We analysed fluctuations in expression of bdccp genes during cultivation in vitro, as well as in cultures treated with different drugs and stimuli. RESULTS: We demonstrated that all B. divergens clonal lines tested, originally derived from naturally infected cows, exhibited sexual stages. Furthermore, sexual commitment was stimulated during continuous growth of the cultures, by addition of specific stress-inducing drugs or by alternating cultivation conditions. Expression of bdccp genes was greatly reduced or even lost after long-term cultivation, suggesting possible problems in the artificial infections of ticks in feeding assays in vitro. CONCLUSIONS: Our research provides insight into sexual development of B. divergens and may facilitate the development of transmission models in vitro, enabling a more detailed understanding of Babesia-tick interactions.
Keywords: Protozoan Proteins; qRT-PCR; Animals; Cattle; bdccp genes; Babesia; arachnida jako vektory; Arachnid Vectors; nemoci skotu; Ticks; Babesia divergens; Babesiosis; babezióza; protozoální proteiny; Gametogenesis; gametogeneze; Gametocytes; zvířata; Transmission; zárodečné buňky; klíšťata; skot; Cattle Diseases; Germ Cells